Real-World Health Care Outcomes and Costs Among Patients With Juvenile Idiopathic Arthritis in Spain - Jordi Antón; Estefania Moreno Ruzafa; Mireia Lopez Corbeto; Rosa Bou; Judith Sánchez Manubens; Sonia Carriquí Arenas; Joan Calzada Hernández; Violetta Bittermann; Carolina Estepa Guillén; Juan Mosquera Angarita; Lucía Rodríguez Díez; Estíbaliz Iglesias; et al. (Journal of Health Economics and Outcomes Research, 2023)
# Background Juvenile idiopathic arthritis (JIA) is the most frequent chronic rheumatic disease in children. If inflammation is not adequately treated, joint damage, long-term disability, and active disease during adulthood can occur. Identifying and implementing early and adequate therapy are critical for improving clinical outcomes. The burden of JIA on affected children, their families, and the healthcare system in Spain has not been adequately assessed. The greatest contribution to direct costs is medication, but other expenses contribute to the consumption of resources, negatively impacting healthcare cost and the economic conditions of affected families.